1996
DOI: 10.1172/jci118723
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of glomerular heat shock protein 27 in experimental nephrotic syndrome.

Abstract: Although nephrotic syndrome is a very common kidney disease, little is known about the molecular changes occurring within glomerular capillary loops during development of disease. The characteristic histologic change is retraction (effacement) of the distal "foot" processes of glomerular epithelial cells (GEC) which surround the capillary loops. The GEC foot processes are an essential part of the kidney's filtration barrier, and their structure is regulated primarily by actin microfilaments, cytoskeletal prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 43 publications
4
66
0
Order By: Relevance
“…The observation that in experimental nephrotic syndrome foot process effacement and proteinuria are paralleled by enhanced HSP27 phosphorylation in the foot processes (32) and that in vitro TNF-␣ enhances transendothelial permeability via a P38-phospho-HSP27 mechanism (16) has led to the hypothesis that HSP27 phosphorylation plays a role Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that in experimental nephrotic syndrome foot process effacement and proteinuria are paralleled by enhanced HSP27 phosphorylation in the foot processes (32) and that in vitro TNF-␣ enhances transendothelial permeability via a P38-phospho-HSP27 mechanism (16) has led to the hypothesis that HSP27 phosphorylation plays a role Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…Both hyperglycemia and glomerular capillary hypertension impose cellular stresses on renal target cells and they are thus potential inducers of a stress response that may counterbalance the deleterious effects of these insults. In addition, enhanced expression/phosphorylation of HSP27, an actin-specific molecular chaperone, has been reported in podocytes in experimental nephrotic syndrome (32), suggesting a role for HSP27 in the pathophysiological changes of the podocyte cytoskeleton during the development of proteinuria. Liu et al (19) have demonstrated that HSP47, a procollagen-specific molecular chaperon, is overexpressed within the glomeruli in both early and advanced diabetic nephropathy, but little is known about the effect of diabetes and diabetes-related insults on other members of this family of proteins.…”
mentioning
confidence: 99%
“…[25][26][27][28][29][30] HSPB1 may be of particular interest in podocyte injury because its expression is induced by the podocyte toxin puromycin aminonucleoside (PAN). 31 Protective cellular responses in podocytes are poorly understood. HSPB1 regulates actin microfilament dynamics in podocyte foot processes.…”
mentioning
confidence: 99%
“…HSPB1 regulates actin microfilament dynamics in podocyte foot processes. 31 In addition, enhanced podocyte HSPB1 expression/phosphorylation has been reported in experimental nephrotic syndrome induced by the podocyte toxin PAN 31 suggesting a role for HSPB1 in the pathophysiological changes of the podocyte cytoskeleton during the development of proteinuria. However, there is an incomplete understanding of the relationship between podocyte HSPB1 and stressors relevant to DN, such as high glucose and Ang II.…”
mentioning
confidence: 99%
“…Enhanced HSP27 expression/phosphorylation in podocytes was reported in experimental nephrotic syndrome, suggesting that HSP27 may regulate polymerization of GEC foot process actin, maintaining normal foot process structure along with its implication in the pathophysiologic changes in these processes during development of the nephrotic syndrome. 70 …”
Section: Hsp27 In Nephrotic Syndromementioning
confidence: 99%